2003
DOI: 10.1097/01.rlu.0000093083.77866.5c
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented Villonodular Synovitis and Giant Cell Tumor of the Tendon Sheath

Abstract: The purpose of this report was to determine the pattern of thallium (T1-201) uptake in pigmented villonodular synovitis (PVNS) and giant cell tumor of the tendon sheath (GCTTS) and to evaluate for features that might help to distinguish these lesions from malignant disease. Scintigraphic images from patients subsequently found to have pigmented villonodular synovitis confirmed by histopathologic analysis were assessed. The patients had been evaluated with T1-201 scintigraphy for a suspicious musculoskeletal le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
0
12
1
Order By: Relevance
“…In fat suppressed images, the mass is high signal and may enhance with thallium Tl-201 scintigraphy (7). However, the MRI can be negative as in the present case.…”
contrasting
confidence: 42%
“…In fat suppressed images, the mass is high signal and may enhance with thallium Tl-201 scintigraphy (7). However, the MRI can be negative as in the present case.…”
contrasting
confidence: 42%
“…1 Increased isotope accumulation (Figures 1 and 2) has been demonstrated for both pigmented villonodular synovitis (PVNS) and giant cell tumours of tendon sheaths (GCTTS) in both early and delayed phase imaging, which may mimic malignant disease. [1][2][3] Recurrent PVNS and GCTTS demonstrate similar 201 TI uptake patterns on early and delayed phase sequences. 4 It has been reported that lesions with low isotope accumulation, suggesting low metabolic activity, are highly unlikely to be PVNS or GCTTS.…”
Section: Introductionmentioning
confidence: 91%
“…10e12 Structural imaging findings in PVNS are well documented. 13 The plain radiographs and ultrasound features are non-specific, 14 but magnetic resonance imaging (MRI), a non-invasive, highly accurate diagnostic modality, is useful in defining extension of disease to nearby tissues. 15 Although radiographic examinations are essential for diagnosis, histology is required to confirm the diagnosis.…”
Section: Introductionmentioning
confidence: 99%